2018
DOI: 10.1111/ejh.13162
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis in neutropenic children with acute leukemia: Do the presently available data really support this practice?

Abstract: Antibiotics are frequently administered for prophylaxis of fever in neutropenic children with cancer. This strategy is mainly derived from adults' data, and various pediatric studies evidenced the effectiveness of antibiotics (eg, fluoroquinolones) in the prevention of febrile neutropenia. However, only two pediatric randomized, doubleblind, placebo-controlled trials have been performed, with a total of 262 leukemic children enrolled, and no other one was ever powered for analyzing effectiveness over other inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 53 publications
2
7
0
2
Order By: Relevance
“…El riesgo en esta población de presentar altos niveles de resistencia a los antibióticos responde a complejos factores sinérgicos intrínsecos del huésped, patógeno y ambiente (múltiples hospitalizaciones, mayor intervención al paciente, uso recurrente de antibioticoterapia empírica de forma inapropiada, comorbilidades asociadas, entre otros) 36,37 .…”
Section: Discussionunclassified
“…El riesgo en esta población de presentar altos niveles de resistencia a los antibióticos responde a complejos factores sinérgicos intrínsecos del huésped, patógeno y ambiente (múltiples hospitalizaciones, mayor intervención al paciente, uso recurrente de antibioticoterapia empírica de forma inapropiada, comorbilidades asociadas, entre otros) 36,37 .…”
Section: Discussionunclassified
“…While the effectiveness of PPX in adult patients has been addressed in several studies, data regarding pediatric patients are limited [ 11 ]. A narrative review by Calitri and colleagues raised questions about antibacterial prophylaxis in children with leukemia, highlighting the lack of strong evidence for its use in the pediatric population [ 12 ]. Moreover, new evidence demonstrated the association of extended-spectrum antibiotic use with the emergence of multidrug-resistant bacteria and gut dysbiosis [ 13 , 14 ], further suggesting a clear risk-benefit assessment.…”
mentioning
confidence: 99%
“…Cephalosporins are broadly used in pediatric patients as well, often as the first line treatment for neutropenic fever [ 57 , 67 ]. Most studies reported a decrease of Enterobacteriacea and an increase of Enterococcus following their administration [ 68 ].…”
Section: Antibioticsmentioning
confidence: 99%